2010
DOI: 10.1111/j.1525-1470.2010.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Porokeratotic Eccrine Duct and Hair Follicle Nevus (PEHFN) Associated with Keratitis-Ichthyosis-Deafness (KID) Syndrome

Abstract: Porokeratotic eccrine ostial and dermal duct nevus is a rare hamartomatous malformation, histologically characterized by cornoid lamellae overlying dilated eccrine ostia. The nevus most commonly presents in the form of multiple filiform keratotic spines in a linear arrangement, usually on the distal extremities. Porokeratotic eccrine and hair follicle nevus is thought to be a variant of porokeratotic eccrine ostial and dermal duct nevus that additionally involves hair follicle infundibula. We report a case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…PAON responded to treatment with tazarotene gel, dithranol short‐contact treatment and topical photodynamic therapy, but laser treatments such as carbon dioxide laser as in our patient and with erbium/carbon dioxide laser appear to be more efficient in most but not all patients . Topical steroids and topical tretinoin seem to be mostly ineffective.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…PAON responded to treatment with tazarotene gel, dithranol short‐contact treatment and topical photodynamic therapy, but laser treatments such as carbon dioxide laser as in our patient and with erbium/carbon dioxide laser appear to be more efficient in most but not all patients . Topical steroids and topical tretinoin seem to be mostly ineffective.…”
Section: Discussionmentioning
confidence: 57%
“…Some patients have coexisting problems such seizures, left hemiparesis Porokeratotic adnexal ostial naevus and scoliosis, 15 deafness and developmental delay, 16 palmoplantar keratoderma, 13 psoriasis, 17,18 hyperthyroidism and polyneuropathy, 11 breast hypoplasia 1 and KID syndrome. 19,20 Recently, PAON is considered as a mosaic form of KID as it may present mutations in a gap junction protein, connexin 26 (Cx26), encoded by the gene GJB2. 21 Cx 26 is in ectodermal tissues as cochlea, cornea and skin.…”
Section: Discussionmentioning
confidence: 99%
“…A functional role for Cx30 is highly likely, as several case studies of Clouston syndrome, associated with mutations in Cx30 have reported the development of eccrine syringofibroadenoma, a rare benign neoplasia associated with the eccrine sweat glands [56]. It is also noteworthy that many patients with dominant mutations in Cx26 develop hyperproliferation in palmoplantar regions, where these glands are highly prevalent [24,57,58].…”
Section: Eccrine Sweat Glandsmentioning
confidence: 99%
“…Unfortunately, the photographs provided in that report were of insufficient quality to confidently make a diagnosis, but the abnormalities might be consistent with PEN. Finally, cases of nonsegmental KID syndrome were recently reported to be “associated with PEN”, on the grounds of purely histopathological findings (Criscione et al , 2010; Lazic et al , 2011). Considering the above, we hypothesized that PEN might be caused by Cx26 mutations associated with KID syndrome or similar hyperkeratotic gap junction disorders (de Zwart-Storm et al , 2009).…”
Section: Introductionmentioning
confidence: 99%